2017
DOI: 10.23917/forgeo.v31i2.5336
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Tourism Development: the Adaptation and Resilience of the Rural Communities in (the Tourist Villages of) Karimunjawa, Central Java

Abstract: Abstract. From 2009 to 2015, the growth of tourism in the tourist villages (desa wisata) of Karimunjawa underwent rapid progress. However, the level of poverty in Karimunjawa remained high. Nevertheless, the involvement of rural people in the sustainable development of tourism has received only limited discussion. Therefore, this article discusses the rural communities' adaptation and resilience in Karimunjawa with the support of sustainable development planning in tourist villages. It covers the background of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…The number of tourists has a direct effect on the number of restaurant & restaurant businesses. The results of this study are in line with [11], [20], [25]. This means that the number of tourists has a direct influence on the number of restaurant & restaurant businesses.…”
Section: Direct and Indirect Effect Analysissupporting
confidence: 88%
“…The number of tourists has a direct effect on the number of restaurant & restaurant businesses. The results of this study are in line with [11], [20], [25]. This means that the number of tourists has a direct influence on the number of restaurant & restaurant businesses.…”
Section: Direct and Indirect Effect Analysissupporting
confidence: 88%
“…Sustainable tourism development impacts the adaptation and resilience of rural communities with tourism activities. Social resilience will increase in communities with access to information and new knowledge dissemination (Setiawan, Rijanta, & Baiquni, 2017). Mamhoori (2015) found that tourism is the fastest growing industry in the world, creating a lot of jobs, national income; especially, tourism creates the source of the third-largest forex income in the world.…”
Section: Studies On Sustainable Tourism Developmentmentioning
confidence: 99%
“…Liu (2003) mentions four important issues in the development of sustainable tourism which includes: (a) balanced perspectives about the concept of sustainability; (b) encouragement to realize practical and theoretical steps; (c) understanding of the characteristics and dynamics of tourism; and (4) collaboration and synergy between various communities through an interdisciplinary approach. Research by Setiawan et al (2017) in Karimunjawa, showed that the sustainable tourism approach proved effective as one form of adaptation to the changing environment and the global economy.…”
Section: Introductionmentioning
confidence: 99%